Pathophysiological Significance of T-type Ca2+ Channels: Role of T-type Ca2+ Channels in Renal Microcirculation - Koichi Hayashi; Shu Wakino; Koichiro Homma; Naoki Sugano; Takao Saruta (Elsevier, 2005)
Since conventional Ca2+ antagonists, with predominant blockade of L-type voltage-dependent Ca2+ channels, elicit preferential dilation of afferent arterioles, they might ostensibly aggravate glomerular hypertension. Recently, novel Ca2+ antagonists, with inhibitory action on L-/T-type Ca2+ channels, have been reported to dilate both afferent and efferent arterioles. The present review attempted to characterize the renal action of these Ca2+ antagonists and evaluated the consequences following the treatment with these agents. In contrast to conventional Ca2+ antagonists (e.g., nifedipine), novel antagonists (e.g., benidipine, efonidipine) potently dilated afferent and efferent arterioles; their action on efferent arterioles appeared to be mediated by the T-type Ca2+ channel blockade, probably through the inhibition of the intracellular Ca2+ release. The comparison of the anti-proteinuric action in subtotally nephrectomized rats showed that efonidipine exerted more prominent action than nifedipine. Furthermore, Ca2+ antagonists with T-type Ca2+ inhibitory action inhibited renin/aldosterone release and proinflammatory process. Finally, patients with chronic renal disease given a 48-week efonidipine treatment showed reduced proteinuria, and this effect was seen even when mean arterial blood pressure failed to become less than 100 mmHg. Collectively, T-type Ca2+ channel blockade provides beneficial action in renal injury. Various mechanisms serve to protect against renal injury, including systemic/glomerular hemodynamic action and non-hemodynamic mechanisms. Keywords:: renal microcirculation, voltage-dependent Ca2+ channel, renal disease, efonidipine, mibefradil